Serum levels of platelet-derived growth factor BB homodimers are increased in male children with autism - Kajizuka, Masanobu; Miyachi, Taishi; Matsuzaki, Hideo; Iwata, Keiko; Shinmura, Chie; Suzuki, Katsuaki; Suda, Shiro; Tsuchiya, Kenji J.; Matsumoto, Kaori; Iwata, Yasuhide; Nakamura, Kazuhiko; Tsujii, Masatsugu; et al. (Progress in neuro-psychopharmacology & biological psychiatry, 2010)
The neurobiological basis of autism remains poorly understood. To examine the role played by serum cytokines in brain development, we hypothesized that Platelet-Derived Growth Factor (PDGF) and Vascular Endothelial Growth Factor (VEGF) may be associated with pathophysiology of autism. In this study, we screened serum levels of these growth factors in young male subjects with autism. We measured serum levels of PDGF subtypes and VEGF in the 31 male children with autism (6–19 years old) and 31 healthy age- and gender-matched subjects. The serum levels of PDGF-BB in male children with autism ( N = 31, 5624.5 ± 1651.8 pg/mL [mean ± SD]) were significantly higher (two-tailed Student's t-test: p = 0.0188) than those of normal control subjects ( N = 31, 4758.2 ± 1521.5 pg/mL [mean ± SD]). There was a significant and positive correlation (Pearson's r = 0.5320, p = 0.0010) between the serum levels of PDGF-BB and the Autism Diagnostic Interview-Revised (ADI-R) domain C scores, which represent stereotyped patterns of behavior in the children with autism. However, there were no marked or significant correlations between serum PDGF-BB levels and clinical variables, including the other ADI-R scores and Intellectual Quotient (IQ) scores by WAIS-R. There were no significant change and correlations with clinical variables in serum PDGF-AA, PDGF-AB, and VEGF levels in the children with autism. Increased levels of serum PDGF-BB homodimers might be implicated in the pathophysiology of autism.